KEDUDUKAN GUBERNUR SEBAGAI WAKIL PEMERINTAH PUSAT DI DAERAH BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Siregar, Nurliana Br; Haryono, Dodi; ', Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Act No. 23 of 2014 to position the governor in two positions, namely as Head of the Autonomous Region and as representatives of the Central Government in the area. In the implementation of regional autonomy as a deputy governor of the central government has the authority to direct, supervise and coordinate the affairs of local government. However, in practice, the authorities are less effective because of the disharmony between the Governor and the Regent / Mayor. Based on this understanding, the writing of this thesis formulates three formulation of the problem, namely; First, the position of the Governor pursuant to Act No. 23 of 2014 on Regional Government. Second, the factors that affect the disharmony between the Governor and the Regent / Mayor. Third, the political direction of the legal position as deputy governor of the Central Government in the area.This research included in the category of normative juridical research that examines the history of the law and legal principles. In this study the type of library materials is the basic data for research, data sources obtained from the literature, among others, include official documents, books, and research reports tangible. data sources used, the primary data, secondary data and data tertiary, technical data collectors in this research is to use the technique documentation.From the research, there are three main things that can be concluded, first, that the position of the Governor pursuant to Act No. 23 of 2014 on Regional Government there are two, namely: As head of the autonomous regions that perform tasks decentralization, the government district / city is not a subordinate of the Province . As a representative of the central government area, the Regent / Mayor is subordinate. Second, factors that affect the disharmony between the Governor and the Regent / Mayor due to several factors: Conflicts of interest, absence of hierarchical relationship between the Governor and the Regent / Mayor, the Governor's role in carrying out the task of deconcentration do not set out clearly, as deputy governor in the center of the area does not have its own deconcentration device, and presence of the role and duties of the governor's confusion in implementing the monitoring of the district / city. Third, the political direction of the legal position as deputy governor of the center has undergone a transition in terms of election of the Governor. Suggestions writer, to strengthen the position as deputy governor of the Central Government, should the Regent / Mayor follow the instructions Governor, In addition the need for further guidance on the status of the province, the position of the Governor, and the recruitment system in order to strengthen the position as deputy governor of the Central Government in the area.Keywords: Position - Governor - Central Government Representative - Act No. 23 of 2014